2006
DOI: 10.1136/thx.2005.046300
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three ways to determine and deliver pressure during nasal CPAP therapy for obstructive sleep apnoea

Abstract: Background: The simplest method of initiating and maintaining therapeutic continuous positive airways pressure (CPAP) therapy for obstructive sleep apnoea (OSA) has not been established. Methods: Ninety eight subjects with OSA requiring CPAP treatment (more than 10 dips in oxygen desaturation of .4% per hour of sleep study and Epworth Sleepiness Score (ESS) .9) were randomised prospectively to three different methods of CPAP delivery for 6 months: (1) autotitration pressure throughout; (2) autotitration pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 26 publications
1
60
0
Order By: Relevance
“…Nevertheless, the present authors believe that, if desired, the technique could be automated in the future, and that a technique for identifying and gating the ECG, as used by STOOHS et al [4], would probably be necessary. The authors also accept that, from a clinical perspective, a diagnosis that can be used for treatment decisions can be made using a respiratory sleep study alone for many patients with OSA [11]; however, as discussed hereafter, the present authors believe the current observations also to be of interest in some clinical situations. It might be suggested that the oesophageal instrumentation itself would disturb sleep, but this was not the case in the present patients, as evidenced by their total sleep time.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, the present authors believe that, if desired, the technique could be automated in the future, and that a technique for identifying and gating the ECG, as used by STOOHS et al [4], would probably be necessary. The authors also accept that, from a clinical perspective, a diagnosis that can be used for treatment decisions can be made using a respiratory sleep study alone for many patients with OSA [11]; however, as discussed hereafter, the present authors believe the current observations also to be of interest in some clinical situations. It might be suggested that the oesophageal instrumentation itself would disturb sleep, but this was not the case in the present patients, as evidenced by their total sleep time.…”
Section: Discussionmentioning
confidence: 67%
“…Another large prospective multi-center trial compared the effects of a prediction formula, A-CPAP and manual titration, and found that these three methods were equally effective in improving subjective sleepiness and the apnea-hypopnea index (AHI) [6]. This was confirmed in a prospective study performed at home, where different methods of CPAP assessment resulted in comparable clinical outcomes [17]. However, despite increasing evidence that alternative methods for assessment of CPAP are effective, manual titration still prevails in official guidelines, although it is the most labour-intensive and expensive procedure.…”
Section: Introductionmentioning
confidence: 89%
“…Employing a predictive equation represents another potential strategy to identify a therapeutic level of PAP (50,(101)(102)(103)(104). Most studies addressing this issue examined primarily patients with severe OSAH and evaluated relatively small sample sizes without describing power calculations.…”
Section: Pap Titration Strategiesmentioning
confidence: 99%